EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DENGAN GALLERY OF LEARNING PADA POKOK BAHASAN BANGUN RUANG SISI LENGKUNG DITINJAU DARI ADVERSITY QUOTIENT SISWA KELAS VIII SMP N SE-KABUPATEN BOJONEGORO TAHUN PELAJARAN 2013/2014 - Khoirutunnisa, Anis Umi (MAGISTRA, 2015)
TheÂ researchÂ wasÂ conductedÂ withÂ theÂ aimÂ toÂ determine:Â (1)Â whichÂ oneÂ resultsÂ betterÂ mathermatics learningÂ achievementsÂ betweenÂ NHTÂ withÂ galleryÂ ofÂ learning,Â NHTÂ andÂ conventionalÂ learningÂ model,Â (2)Â wich oneÂ resultsÂ betterÂ mathematicsÂ learningÂ achievementsÂ withÂ climbers,campersÂ orÂ quittersÂ (3)Â onÂ eachÂ learning models,Â whichÂ oneÂ givesÂ betterÂ mathematicsÂ learningÂ achievementsÂ studentsÂ withÂ climbers,campersÂ orÂ quitters (4)Â onÂ eachÂ climbers,campersÂ orÂ quitterswichÂ oneÂ givesÂ betterÂ mathematicsÂ achievementsÂ betweenÂ NHTÂ with galleryÂ ofÂ learning,Â NHTÂ orÂ conventional.Â ThisÂ studyÂ wasÂ aÂ quasiÂ experimentalÂ researchÂ withÂ 3x3Â factorial designs.Â TheÂ balancedtestÂ ofÂ theÂ previousÂ dataÂ (theÂ resultÂ ofÂ UAS)wasÂ analyzedÂ usingÂ oneÂ wayÂ ANOVA.Â The conclusionÂ showsÂ thatÂ theÂ threeÂ classesÂ haveÂ balanceÂ ability.Â TheÂ hypothesesÂ testingÂ usedÂ unbalancedÂ twoÂ ways ANOVA.TheÂ conclutionÂ ofÂ theÂ researchÂ wereÂ asfollows:Â (1)Â TheÂ studentsÂ withÂ NHTÂ withÂ GalleryÂ ofÂ learning modelsÂ haveÂ betterÂ learningÂ achievementÂ thanÂ theÂ studentsÂ withÂ NHTÂ learningÂ modelsÂ andÂ conventional,Â and NHTÂ learningÂ modelsÂ haveÂ betterÂ achievementÂ thanÂ thoseÂ withÂ conventionalÂ learning;Â (2)Â theclimbersÂ have betterÂ mathematicsÂ achievementÂ thanÂ campersÂ andÂ quitters,Â andÂ theÂ camperstheÂ achievementÂ areÂ betterÂ Â than thoseÂ quitters;Â (3)Â a.Â InÂ theÂ NHTÂ withÂ galleryÂ oflearningÂ model,Â thereÂ wasÂ noÂ differenceÂ inÂ learningÂ achievement inÂ eachÂ criterionÂ ofÂ Adversity QuotientÂ (climbers,campersandquitters);b.Â InÂ theÂ NHTÂ learningÂ models,Â the climbersandÂ camperstheÂ mathematicsÂ achievementÂ wereÂ betterÂ thanÂ quitters;Â c.Â InÂ theÂ conventionalÂ learning models,Â theÂ camperâsÂ mathematicsÂ achievementÂ areÂ betterÂ thanÂ climbersandÂ quitters,Â andÂ theÂ campersthe achievementÂ betterÂ thanÂ quitters.Â (4)Â Â a.Â ForÂ theÂ climbers,Â thereÂ wasÂ noÂ differenceÂ inÂ learningÂ achievementÂ in eachÂ learningÂ models;Â b.Â ForÂ theÂ campersNHTÂ withÂ galleryÂ learningÂ andÂ NHTÂ betterÂ thanÂ conventionalÂ learning ;c.Â ForÂ theÂ quittersNHTÂ withÂ GalleryÂ ofÂ learningÂ modelÂ produceÂ betterÂ mathematicsÂ achievementÂ thanÂ NHT learningÂ modelÂ andÂ ConventionalÂ learning. Kata kunci:NHTwith gallery of learning,Â NHT,Â conventional,Â Adversity quotient, andmathematicsÂ learning achievements.